Anesthetic Management of Patients with a Type A Aortic Dissection - G. Silvay; M. Khromava; M. Weiner; J. G. Augoustides; J. G. Castillo (Общая реаниматология, 2019)
«It is type of surgery that is not for the lone operator… Team is of course essential in the operating theater, where in addition to the surgical and nursing assistants, the anesthesiologist plays a part of fundamental importance which deserves a special tribute.»  Russel C. Brock, 1949 Deep hypothermic circulatory arrest (DHCA) for the adult aortic arch repair is still associated with significant mortality and morbidity. Furthermore, there is significant variation in the conduct of this complex perioperative technique. The variation in the practice of DHCA has not been adequately characterized and may offer multiple therapeutic opportunities for outcome enhancement and reduction of procedural risk. The International Aortic Arch Study Group (IAASSG) was recently organized to investigate an optimal neuroprotection during the thoracic aortic reconstruction.